Health Information: A Case Report of Outbreak Salmonella Infection in "Kinder Chocolate", How in Indonesia? - Fikri, Elanda; Firmansyah, Yura Witsqa; Husna, Riyana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Salmonella is an agent that can cause foodborne diseases. Serotype Typhimurium is the cause of outbreaks in the age group under 10 years and children in 2022. Kinder trademark chocolate products have been identified as being contaminated with Salmonella typhimurium. Case reports on April 25, 2022, against Salmonella typhimurium infection reached 151 cases in various countries. The source of the contamination was discovered during the manufacturing process for buttermilk, worker hygiene, and poor equipment sanitation at a chocolate plant in Arlon, Belgium. The food industry must discipline the application of the HACCP system, which is an important instrument in food safety management to prevent and control the spread of infection. Abstrak: Salmonella adalah agen yang dapat menyebabkan penyakit tular pangan. Serotipe typhimurium adalah penyebab wabah pada kelompok usia di bawah 10 tahun dan anak-anak pada tahun 2022. Produk cokelat merek dagang Kinder telah diidentifikasi terkontaminasi Salmonella typhimurium. Laporan kasus pada 25 April 2022, infeksi Salmonella typhimurium mencapai 151 kasus di berbagai negara. Sumber kontaminasi ditemukan selama proses pembuatan buttermilk, kebersihan pekerja, dan sanitasi peralatan yang buruk di pabrik cokelat di Arlon, Belgia. Industri makanan harus mendisiplinkan penerapan sistem HACCP, yang merupakan instrumen penting dalam manajemen keamanan pangan untuk mencegah dan mengendalikan penyebaran infeksi.